Given the adjacent angles \( m∠1 \) and \( m∠2 \) such that their sum is \( 160^\circ \):
- \( m∠1 = 3x \)
- \( m∠2 = 2x + 10 \)
The equation representing the sum of the angles is:
\[ m∠1 + m∠2 = 160^\circ \]
Substituting the expressions for \( m∠1 \) and \( m∠2 \):
\[ 3x + (2x + 10) = 160 \]
Now, combine like terms:
\[ 3x + 2x + 10 = 160 \]
\[ 5x + 10 = 160 \]
Next, subtract 10 from both sides:
\[ 5x = 150 \]
Now, divide both sides by 5:
\[ x = 30 \]
Now that we have \( x \), we can find the measurements of the angles:
-
\( m∠1 \): \[ m∠1 = 3x = 3(30) = 90^\circ \]
-
\( m∠2 \): \[ m∠2 = 2x + 10 = 2(30) + 10 = 60 + 10 = 70^\circ \]
Thus, the measurements are:
- \( m∠1 = 90^\circ \)
- \( m∠2 = 70^\circ \)